An evaluation of dermal microcirculatory occlusion under repeated mechanical loads: Implication of lymphatic impairment in pressure ulcers. (13th July 2020) - Worsley, Peter R.; Crielaard, Hanneke.; Oomens, Cees W. J.; Bader, Dan L.
Abstract: Objective: Pressure ulcers are caused by prolonged mechanical loads deforming the underlying soft tissues. However, the mechanical loads for microcirculatory occlusion are unknown. The present study was designed to characterize the simultaneous response of microvascular and lymphatic structures under repeated mechanical loading. Methods: The effects of two distinct loading/unloading cycles involving (a) incremental pressures 30, 60, and 90 mmHg and (b) three repeated cycles of 30 mmHg were evaluated on a cohort of able‐bodied volunteers. Microvascular response involved the monitoring of transcutaneous gas tensions, while dermal lymphatic activity was estimated from near‐infrared imaging. Responses were compared during each load and recovery cycle. Results: Changes in microvascular response were dependent on the load magnitudes, with 30 mmHg resulting in a reduction in oxygen tension only, while 90 mmHg affected both oxygen and carbon dioxide values in most cases (54%). By contrast, lymphatics revealed near total occlusion at 30 mmHg. Although there were intersubject differences, temporal trends consistently revealed partial or full impairment under load, with recovery during off‐loading. Conclusions: The pressure required to cause microcirculatory occlusion differed between individuals, with lymphatic impairment occurring at a lower pressure to that of microvascular vessels. This highlights the need for personalized care strategies and regular off‐loading of vulnerable tissues.